Analysis of Community Based Tourism Development to Increase SME Performance and Welfare Level. Case Study in West Sumatra - SUPRIYADI, Edy; IHA, Haryani Hatta; DJAMIL, Achmad; DHARMA, Putra (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018, 2019)
This study evaluates the perception of developing community-based tourism (CBT) as a strategy of developing community-based tourist destination in West Sumatra located in solok and Pesisir Selatan district. This study aims to examine the relationship between independent variables such as Infrastructure, Social Capital Potential, Commitment, government policy with dependent variable Development of MSME and Public Welfare with intermediary variables consisting of Collaboration, CBT tourism destination. Population is all tourists in West Sumatra province and samples taken in several the owner of SME areas using multistage cluster purposive sampling method. Statistical analysis using SEM Structural Equation Modelling analysis with PLS software. The results are obtained that Infrastructure, commitment, Social Networking, the role of government have a positive and significant influence on collaboration. There is sufficient mediation to play a role of the collaboration component that links between Infrastructure, Commitment, Social Networking, the role of governments with CBT. The development of CBT has an effect on creating job opportunities and developing SMEs.